Pembuatan Kebun Percontohan berbasis Plot Temporer sebagai Upaya Mendukung Kemandirian Pangan di Kelurahan Sa’dan Matallo - Paliling, Formanto; Simon, Christof Geraldi; Lasarus, Risa; Ambabunga, Yusri Anugerah Manapa; Limbongallo, Yusri; Dendo, Ermitha Ambun Rombe (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2026)
This community service activity aims to improve the utilization of yard land as an effort to support community food self-sufficiency in Sa’dan Matallo Village, Sa’dan District, North Toraja Regency. The program is implemented through the creation of a temporary plot-based demonstration garden with the active involvement of students and the local community. Implementation methods include observation and location identification, preparation of tools and materials, land preparation, making beds, planting vegetable seeds, plant maintenance, education, and activity evaluation. The types of plants cultivated are chili and kale because they are easy to grow and have a relatively short harvest period. The results of the activity indicate that the demonstration garden program is able to increase community knowledge and awareness regarding the importance of utilizing yard land as a source of family food. In addition, the community began to understand the basic techniques of simple plant cultivation that can be applied independently in their respective homes. This program not only provides benefits in meeting household food needs, but also serves as a medium for education and community empowerment in supporting sustainable food security.